Labor Market Information System: A Review of Some Practices - Shrestha, Rajendra (Journal of Technical and Vocational Education and Training, 2024)
Accurate and up-to-date labor market information system, which is conducted with the involvement of public decision markers, technical and vocational education and training (TVET) practitioners, employers and their associations, employee associations, training providers and learners, is an essential feature of a successful TVET system. Similarly, engagement of multiple TVET stakeholders is an important component of overall skills development system which leads to developing responsive labor market skill needs, supporting prioritized economic sectors to foster dialogue among the stakeholders to maintain balance demand and supply of labor right. It enhances integration of labor market requirements in the overall training and skills development cycle and ensures that trainees acquire market-relevant skills for their employability and self-employment. In the context of changing labor market conditions, collecting, compiling, analyzing, and disseminating current and future needs from the TVET customers can support better matching for training and employment. As labor markets are constantly evolving and changing, labor market analysis therefore needs to be conducted on a regular basis so that real time labor market information can be obtained. But the active and regular labor market information process is underexplored in a developing country like Nepal. The main objective of the article is to explore the common practices of Nepali labor market information system and the problems faced by the TVET system. Thus, the article addresses the information gap by diving deep into the clear understanding of labor market, practices of labor market information processes in some South Asian countries, including Nepal and issues and challenges facing the Nepali labor market information process.